Preliminary study of the key hormones regulating reproduction in the bluefin tuna (BFT): The brain gonadotropin-releasing hormones (GnRHs) and the pituitary gonadotropins, FSH and LH - Rosenfeld H.; Gordin H.; Klenke U.; Zohar Y. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
As a first step towards understanding the spatio-temporal profiles of the key reproductive hormones in bluefin tuna (BFT; Thunnus thynnus), the present study was aimed to assess the available immunological tools to detect the gonadotropin (GtH) LH and the gonadotropin-releasing hormone (GnRH) isoforms in tuna species. Our preliminary studies demonstrated that the heterologous ELISA, developed to measure striped bass LH (stbLH), successfully determined LH levels in pituitaries and plasma of bonito (Sarda sarda) and yellowfin tuna (T. albacares). In addition, our specific ELISAs for GnRH isoforms successfully detected the salmon GnRH (sGnRH) and the sea bream GnRH (sbGnRH) in pituitary extracts of bonito and yellowfin tuna. Although we could not detect the chicken GnRH-II (cGnRH-II) isoform, we assume that our failure to detect this particular isoform in tuna is technical, and that tuna species, like other perciform fish, possess the three GnRH isoforms: sbGnRH, sGnRH and cGnRH-II.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)